Food hoarding of an avian predator: sex- and age-related differences under fluctuating food conditions - Giulia Masoero; Chiara Morosinotto; Toni Laaksonen; Erkki Korpimäki (SPRINGER, 2022)
Hoarding behaviour (storing food for a later use) has evolved to reduce starvation risk when resources are scarce. Different age and sex classes often show differences in foraging due to experience, skills or life history strategy, but such differences in hoarding under spatio-temporally varying environmental conditions have rarely been studied in the wild. We studied hoarding behaviour of Eurasian pygmy owls (Glaucidium passerinum) during 2003-2016 in western Finland, where the abundance of their main prey (voles) fluctuates in three-year population cycles. In 14years, 1056 food stores were found during the hoarding season (Oct-Dec) and 330 pygmy owls were trapped at these stores. The number of stores per individual did not vary in relation to age, sex or vole abundance. Adults (+1-year old) had their stores farther apart than yearlings. Both the number of stores per year and the biomass of stored prey items increased with vole abundance. Females and yearlings had larger and heavier stores than males and adults, respectively. The same individuals stored more food as yearlings than as adults. These sex- and age-differences in hoarding indicate that it is not constrained by experience or skills. It rather seems that less-experienced yearlings rely more on stored food than adults. Females may need more food due to their larger size and need to accumulate energy reserves before reproduction. A detailed knowledge of age- and sex-related differences in hoarding behaviour under fluctuating abundances of main foods is fundamental to better understand a population response to climate change and forest management.Significance statementThe hoarding behaviour of animals has evolved to cope with the problem of food limitation. On the basis of 14-year data from pygmy owls, we show that the number of stores per year and the biomass of prey items per store increased with vole abundance in the environment. Adults had stores farther apart than yearlings, and females and yearlings stored more prey items and biomass compared to males and adults, respectively. These results indicate that hoarding behaviour responds to the available main prey abundance and varies with traits such as age and sex. Because different age and sex classes might respond differently to variation in food abundance, due to habitat alterations or climate change, a detailed knowledge of hoarding behaviour can be of particular importance to understand changes in body condition, reproductive success and survival of pygmy owls under changing climate and management of boreal forest.